Lack of Communication and Transparency: Leadership in Strengthening an Inclusive Organizational Culture - Yusan Atryscha Venariza; Nadia Sari; Clément Chaisemartin (JIECIs - Journal of Islamic Economics and Contemporary Issues, 2026)
This study examines the role of leadership in strengthening inclusive organizational culture, with a particular focus on communication and transparency. Effective leadership not onlyguides organizations toward achieving their goals but also plays a crucial role in fosteringanopen, fair, and participatory work environment. However, many organizations in Indonesiastill face challenges related to ineffective communication and limited transparency, whichnegatively affect trust, employee engagement, and the development of an inclusiveorganizational culture. This research employs a descriptive quantitative approach, utilizingobservation and literature review as data collection methods. The findings indicate that thelack of two-way communication and leadership transparency significantly hinders theimplementation of an inclusive organizational culture. Therefore, the applicationofcommunicative, transparent, and inclusive leadership is essential to creating a collaborative, harmonious, and sustainable organizational environment